Drowning in urban growth: rethinking flood resilience and spatial equity in Lagos, Nigeria - Dossa, Kossivi Fabrice; Miassi, Yann Emmanuel; Bakary, Sofwaan; Ogou, Faustin Katchele (Frontiers in Sustainable Resource Management, 2025)
IntroductionUrban flooding in Africa, intensified by climate change, poses a major challenge to sustainable urban development. In megacities like Lagos, the relationship between rapid urbanization and increased flood risk remains underexplored. This study investigates the interactions between urban expansion and flood occurrence in Lagos, identifies key contributing factors, and proposes strategies to enhance urban resilience.MethodsUrbanization data were obtained from the UN-Habitat database, while flood data were sourced from the Emergency Events Database (EM-DAT) maintained by the Centre for Research on the Epidemiology of Disasters. Time series analysis was combined with qualitative review of secondary data to examine trends, spatial distribution of floods, and underlying causes.ResultsNigeria has experienced dynamic urban growth, with Lagos' population increasing from 7.28 million (1995–2000) to 17.15 million (2020–2025), a growth rate 2.4 times higher than the national average. Spatial analysis identified Lagos as a flood hotspot, with 35 recorded events-particularly concentrated in Victoria Island's Lekki area (7 events) and in Kosofe, Ikeja, and Agege districts (3 events each). Contributing factors fall into four categories: environmental, socio-economic, institutional, and structural. Flood impacts include agricultural land degradation, water pollution, erosion, infrastructure damage, crop loss, poverty aggravation, and public health risks such as the spread of infectious diseases.DiscussionDespite resilience measures such as modern infrastructure (e.g., the Great Wall of Lagos) and institutional frameworks (e.g., Lagos State Emergency Management Agency), effectiveness is hindered by governance issues, limited trust, and insufficient community engagement. Strengthening communication, integrating climate-tailored early warning systems, and fostering active community participation in flood management could enhance trust and long-term resilience.